Characterization of abiotic coaditions affecting vegetation distribution in the river plate coastal plain, Argentina - Giménez, Jorge E. (2008)
The river Plate coastal plain is located in northeastern Buenos Aires province, where geological events such as sea transgressions and regressions in the Holocene have produced a stratigraphic column with marine-estuarine, fluviatile and continental sediments, as well as a variety of landforms and soils. The aim of this paper is to describe these different coastal settings and their influence in the distribution of plant communities.